Job satisfaction and animal welfare at slaughter: A survey of Official Veterinarians in the United Kingdom and Republic of Ireland - Imogen O’Connor; Kelly Gouveia (Animal Welfare)
In the UK and the Republic of Ireland, Official Veterinarians (OVs) are employed by the Food Standards Agency and the Food Safety Authority, respectively, as legal authorities for both animal welfare and food safety. However, little is known about job satisfaction in this profession which has the potential to impact professionals’ well-being and performance. Moreover, despite animal welfare issues being a reality that OVs witness, we do not yet understand how OVs perceive these issues at slaughter or whether this impacts job satisfaction. We assessed OVs’ perceptions on job satisfaction and views on welfare at slaughter across the UK and ROI, through an online questionnaire with 113 participants, which included socio-demographic information of participants and questions or statements about different aspects of job satisfaction and animal welfare issues at slaughter. While most OVs committed to their work they reported issues that may compromise job satisfaction, such as often experiencing loneliness at work, threatening situations and sleep disorders. Moreover, job satisfaction was often impacted by animal welfare incidents, and conflicts with food business operators were considered one of the greatest barriers to improving welfare at slaughter. There is also the likelihood of professionals’ individual ethical values being challenged since OVs are virtually certain to witness religious slaughter yet disagree with this practice to the extent that they consider it should be banned. We reveal significant challenges associated with the role of OV that justify creation of a support network to assist and safeguard this profession, as well as animal welfare at slaughter.